2021
DOI: 10.1007/s11769-021-1228-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal Differentiation in the Incidence of Influenza and Its Relationship with Air Pollution in China from 2004 to 2017

Abstract: The Healthy China Initiative is a major health strategy being pursued by the country. To prevent and control different types of diseases as well as their complex variants, research on the spatio-temporal differentiation among and mechanisms of influence of epidemic diseases is growing worldwide. This study analyzed monthly data on the incidence of influenza by using different methods, including Moran’s I , the hotspot analysis model, concentration analysis, and correlation analysis, to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…According to the findings, the air quality in Jiangsu improved dramatically throughout the epidemic prevention and control period compared to the preceding three years. This is clearly in line with the pandemic prevention and control measures implemented in Jaingsu, namely traffic restrictions, closed community management, and enterprise production and operation control [33][34][35]. These severely limited people's production and living activities, which is closely tied to the reduction in pollution.…”
Section: Change Of Nomentioning
confidence: 62%
“…According to the findings, the air quality in Jiangsu improved dramatically throughout the epidemic prevention and control period compared to the preceding three years. This is clearly in line with the pandemic prevention and control measures implemented in Jaingsu, namely traffic restrictions, closed community management, and enterprise production and operation control [33][34][35]. These severely limited people's production and living activities, which is closely tied to the reduction in pollution.…”
Section: Change Of Nomentioning
confidence: 62%
“…The incidence and coverage of tuberculosis, human infection with H7N9 virus, rabies, hemorrhagic fever, malaria, measles, Japanese encephalitis, leptospirosis, influenza A(H1N1) virus infection, and SARS have decreased significantly in the past decade, of which, malaria has almost been eliminated [ 26 , 31 , 50 , 51 , 52 , 59 , 60 , 62 , 64 ]; this may be attributed to the extensive public disease control and ecological and health improvement in China [ 52 ]. However, dengue, syphilis, hepatitis C, AIDS, brucellosis, HFMD, and influenza showed the opposite trend because of the rapid development of tourism and the considerable increase in the migrant population in recent years [ 7 , 11 , 22 , 55 , 58 , 80 , 90 ]. Through spatiotemporal analyses of the included studies, it was found that the primary clusters of dengue, hemorrhagic fever, syphilis, Japanese encephalitis, anthrax, hepatitis C, brucellosis, HFMD, and human infection with H7N9 virus were expanding [ 11 , 22 , 24 , 26 , 31 , 43 , 65 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, dengue, syphilis, hepatitis C, AIDS, brucellosis, HFMD, and influenza showed the opposite trend because of the rapid development of tourism and the considerable increase in the migrant population in recent years [ 7 , 11 , 22 , 55 , 58 , 80 , 90 ]. Through spatiotemporal analyses of the included studies, it was found that the primary clusters of dengue, hemorrhagic fever, syphilis, Japanese encephalitis, anthrax, hepatitis C, brucellosis, HFMD, and human infection with H7N9 virus were expanding [ 11 , 22 , 24 , 26 , 31 , 43 , 65 , 80 ]. These diseases have a common tendency to spread to the west and inland areas, which was explained by the included studies, as the phenomenon might be related to the increase in population mobility and improvement of transportation infrastructure that has made less developed and inland areas more closely connected with the outside world [ 64 , 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas in larger cities non-climate factors have a more profound influence and a milder response to climate factors is found. Outdoor, as well as indoor, air pollution are associated with higher influenza incidence, and increased severity of the health risks related to the virus, particularly in winter months with low temperatures (Meng et al, 2021;Murtas and Russo, 2019;Song et al, 2021;Su et al, 2019;Toczylowski et al, 2021;Wang et al, 2016). Studies show a positive association between higher influenza risks and people who suffer from asthma as well as other respiratory allergies, obesity, or are recipient of a treatment for a chronic disease (Guerrisi et al, 2019;Hirota et al, 1992;Jain and Chaves, 2011;Karki et al, 2018;Yang et al, 2013).…”
Section: Implications For the Impact Casesmentioning
confidence: 99%